SOSIALISASI FERMENTASI PAKAN DAN MANAJEMEN REPRODUKSI SERTA PELATIHAN PEMBUATAN COMPLETE FEED PADA PETERNAK RUMINANSIA KECIL - Liman Liman; Muhammad Mirandy Pratama Sirat; Syahrio Tantalo; Erwanto Erwanto; Ratna Ermawati; Lusia Komala Widiastuti (Jurnal Media Tropika, 2026)
The PKM DIPA FP Unila team aimed to enhance the knowledge and technical skills of small ruminant farmers partnered with Teo Farm through a series of six integrated activities conducted from June to July 2025 through: (1) outreach and focused discussions on feed fermentation technology and reproductive management of small ruminants; (2) hands-on training on feed fermentation for the production of complete feed; (3) evaluation of the complete feed through organoleptic assessment, palatability testing, and proximate analysis; (4) provision of mineral premix supplementation; and (5) monitoring and evaluation of program implementation by collecting and analyzing data on the percentage increase in pre-test and post-test scores, based on a structured questionnaire, with results presented in tabular and graphical formats. The outcomes were as follows: 1) extension and training activities were attended by 14 farmers; 2) training on the production of fermented complete feed using a silage method over a 21-day period resulted in three containers with a capacity of 200 kg each; 3) organoleptic evaluation indicated very good quality with high palatability; 4) proximate analysis of the complete feed on a dry matter basis showed 15.89% crude protein, 2.21% crude fat, 30.75% crude fiber, 77.79% moisture content, 13.33% ash content, 37.82% NFE; 5) each farmer received 1 kg of mineral premix; and 6) participants’ knowledge levels increased from 42.86% to 85.71%. In conclusion, outreach on feed fermentation and reproductive management, combined with training in the production of silage-based complete feed, effectively improved the knowledge and skills of small ruminant farmers from a low to a high category, with an overall increase of 42.85%.